Overview of Domestic and Agricultural Pesticides Use Contributing to Aedes aegypti Resistence in Ambarawa Subdistrict, Indonesia (Unnes Journal of Public Health, 2021)
Ambarawa Sub District Semarang District is an endemic area of DHF. Furthermore, the year 2019 recorded an increase in the IR and CFR by 271.73, and 1.123% respectively. Insecticide resistance contributed to the increase in DHF cases. Therefore, this study aims to determine the description of community behavior concerning the use of household and agricultural insecticide which lead to insecticide resistance in Aedes aegypti. This type of research is descriptive using qualitative methods. The informants are insecticide users in Ambarawa subdistrict. Twenty-four sample is choosen by purposive sampling. In-depth interview is carried out for the data collection. Data analysis used is data reduction, data presentation, and data verification using the manual way. As the result of the study, most of the subjects experienced a decrease in the effectiveness of insecticides, caused by poor community knowledge, and behavior of people who did not apply any insecticide resistance management guidelines. Considering the condition of current insecticide circulation, the government needs to make policies relating to the management of insecticide resistance